Analysis of Needs for Developing KAPAL PINISI Application (Smart Literacy Adventure Activity) Based on Local Wisdom to Form 6C Skills of Indonesian Society - Damariswara , Rian; Laila , Alfi; Mujiwati , Endang Sri; Nurkholidah, Manfia; Afandi, Saiful (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
Basic literacy is an important foundation in education in Indonesia, but there are still challenges in literacy skills for students and teachers. Local wisdom, which should be a relevant source of learning, is often ignored in the curriculum. This study aims to describe: (1) the need to develop the KAPAL PINISI application (Smart Literacy Adventure Activities); (2) obstacles encountered in developing the application; (3) support for the development of applications based on local wisdom, with a focus on the formation of 6C skills (Critical thinking, Creativity, Collaboration, Communication, Citizenship, Character) in Indonesian society. The data collection method used a need assessment questionnaire distributed to students, teachers, and parents in several regions. This study used a mixed method approach (qualitative and quantitative) with 200 fifth grade students and 40 teachers in ten elementary schools spread across Indonesia. The data analysis technique used descriptive statistics on quantitative data and source triangulation techniques (Miles and Huberman) on qualitative data. The results of the analysis show that respondents want an application that integrates local wisdom, as well as interactive features that support collaborative and communicative learning. The obstacles faced by teachers are; never having used teaching materials based on local wisdom that are integrated into the android application. The support for the development of the KAPAL PINISI application is that the principal provides training facilities and workshops based on local wisdom to teachers, and helps teachers be creative in making teaching media. The development of the KAPAL PINISI Application based on local wisdom is an important and effective step. So that the results of the study can be used as a reference for further research in the form of developing teaching media for the KAPAL PINISI Application based on local wisdom in Indonesia.